Applications of three-dimensional carbon nanotube networks - Scarselli, Manuela; Castrucci, Paola; De Nicola, Francesco; Cacciotti, Ilaria; Nanni, Francesca; Gatto, Emanuela; Venanzi, Mariano; De Crescenzi, Maurizio (Beilstein Journal of Nanotechnology, 2015)
In this paper, we show that it is possible to synthesize carbon-based three-dimensional networks by adding sulfur, as growth enhancer, during the synthesis process. The obtained material is self-supporting and consists of curved and interconnected carbon nanotubes and to lesser extent of carbon fibers. Studies on the microstructure indicate that the assembly presents a marked variability in the tube external diameter and in the inner structure. We study the relationship between the observed microscopic properties and some potential applications. In particular, we show that the porous nature of the network is directly responsible for the hydrophobic and the lipophilic behavior. Moreover, we used a cut piece of the produced carbon material as working electrode in a standard electrochemical cell and, thus, demonstrating the capability of the system to respond to incident light in the visible and near-ultraviolet region and to generate a photocurrent.
Keywords: carbon nanotube sponge; electrochemical; hydrophobicity; lipophilicity

(untitled) - Zhao, D.; Yang, P.; Melosh, N.; Feng, J.; Chmelka, B. F.; Stucky, G. D. (Adv. Mater., 1998)

(untitled) - Nardecchia, S.; Carriazo, D.; Ferrer, M. L.; Gutiérrez, M. C.; del Monte, F. (Chem. Soc. Rev., 2013)

(untitled) - Lee, J.; Kim, J.; Hyeon, T. (Adv. Mater., 2006)

(untitled) - Gui, X.; Wei, J.; Wang, K.; Cao, A.; Zhu, H.; Jia, Y.; Shu, Q.; Wu, D. (Adv. Mater., 2010)

(untitled) - Li, H.; Gui, X.; Zhang, L.; Wang, S.; Ji, C.; Wei, J.; Wang, K.; Zhu, H.; Wu, D.; Cao, A. (Chem. Commun., 2010)

(untitled) - Gui, X.; Li, H.; Wang, K.; Wie, J.; Jia, Y.; Li, Z.; Fan, L.; Cao, A.; Zhu, H.; Wu, D. (Acta Mater., 2011)

(untitled) - Qian, W.; Gu, Z.-Z.; Fujishima, A.; Sato, O. (Langmuir, 2002)

(untitled) - Moura, F. C. C.; Lago, R. M. (Appl. Catal., B, 2009)

(untitled) - Cao, A.; Dickrell, P. L.; Sawyer, W. G.; Ghasemi-Nejhad, M. N.; Ajayan, P. M. (Science, 2005)

(untitled) - García-Martínez, J.; Lancaster, T. M.; Ying, J. Y. (Adv. Mater., 2008)

(untitled) - You, B.; Jiang, J.; Fan, S. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Bryning, M. B.; Milkie, D. E.; Islam, M. F.; Hough, L. A.; Kikkawa, J. M.; Yodh, A. G. (Adv. Mater., 2007)

(untitled) - Camilli, L.; Pisani, C.; Gautron, E.; Scarselli, M.; Castrucci, P.; D’Orazio, F.; Passacantando, M.; Moscone, D.; De Crescenzi, M. (Nanotechnology, 2014)

(untitled) - Camilli, L.; Pisani, C.; Passacantando, M.; Grossi, V.; Scarselli, M.; Castrucci, P.; De Crescenzi, M. (Appl. Phys. Lett., 2013)

(untitled) - Tibbetts, G. G.; Bernard, C. A.; Gorkiewicz, D. W.; Alig, R. L. (Carbon, 1994)

(untitled) - Romo-Herrera, J. M.; Sumpter, B. G.; Cullen, D. A.; Terrones, H.; Cruz-Silva, E.; Smith, D. J.; Meunier, V.; Terrones, M. (Angew. Chem., Int. Ed., 2008)

(untitled) - Calliari, L.; Fanchenko, S.; Filippi, M. (Carbon, 2007)

(untitled) - Castrucci, P.; Scilletta, C.; Del Gobbo, S.; Scarselli, M.; Camilli, L.; Simeoni, M.; Delley, B.; Continenza, A.; De Crescenzi, M. (Nanotechnology, 2011)

Physical Chemistry of Surfaces - Adamson, W.; Gast, A. P. (John Wiley & Sons, 1997)

(untitled) - Cassie, A. B. D.; Baxter, S. (Trans. Faraday Soc., 1944)

(untitled) - De Nicola, F.; Castrucci, P.; Scarselli, M.; Nanni, F.; Cacciotti, I.; De Crescenzi, M. (Nanotechnology, 2015)

(untitled) - De Nicola, F.; Castrucci, P.; Scarselli, M.; Nanni, F.; Cacciotti, I.; De Crescenzi, M. (Sci. Rep., 2015)

(untitled) - Quéré, D. (Nat. Mater., 2002)

(untitled) - Peng, X.; Li, Y.; Luan, Z.; Di, Z.; Wang, H.; Tian, B.; Jia, Z. (Chem. Phys. Lett., 2003)

(untitled) - Shan, C.; Zhao, W.; Lu, X. L.; O’Brien, D. J.; Li, Y.; Cao, Z.; Elias, A. L.; Cruz-Silva, R.; Terrones, M.; Wei, B.; Suhr, J. (Nano Lett., 2013)

(untitled) - Chen, J.; Meng, F.; Gui, X.; Sun, H.; Zeng, H.; Li, Z.; Zhou, Y.; Tang, Z. (Carbon, 2012)

(untitled) - Castrucci, P.; Tombolini, F.; Scarselli, M.; Speiser, E.; Del Gobbo, S.; Richter, W.; De Crescenzi, M.; Diociaiuti, M.; Gatto, E.; Venanzi, M. (Appl. Phys. Lett., 2006)

(untitled) - Scarselli, M.; Camilli, L.; Matthes, L.; Pulci, O.; Castrucci, P.; Gatto, E.; Venanzi, M.; De Crescenzi, M. (Appl. Phys. Lett., 2012)

(untitled) - Scarselli, M.; Castrucci, P.; Camilli, L.; Del Gobbo, S.; Casciardi, S.; Tombolini, F.; Gatto, E.; Venanzi, M.; De Crescenzi, M. (Nanotechnology, 2011)

(untitled) - Kuhn, H. J.; Braslavsky, S. E.; Schmidt, R. (Pure Appl. Chem., 1989)